Type-noun binominals in four Romance languages. (January 2016) - Mihatsch, Wiltrud
Abstract: Binominal constructions with originally taxonomic nouns such English sort, kind and type show a great variety of weakly grammaticalized uses. The aim of this paper is to establish a classification of the different subtypes of these binominals in French, Italian, Portuguese and Spanish on the basis of C-ORAL-ROM, a comparative Romance corpus of oral data and other corpora, and to try and explain the links between the different construction types. The syntax and semantics of these binominals in four genetically related languages show that approximator uses of type nouns which are cognates of species are the most strongly grammaticalized binominals, although less grammaticalized than the English equivalents sort and kind . Other functions such as postdeterminer uses rather tend to be expressed by the cognates of type, much more recent taxonomic nouns. These functions arise very easily due to the ambiguity of type-noun constructions between type and instance readings. Highlights: Binominals containing taxonomic nouns. Grammaticalization of type noun binominals. Comparison of French, Italian, Portuguese and Spanish.